An Overly Permissive Extension. (July 2016) - Kagan, Jerome
In this article, I describe how the current practice of classifying as a stressor any event that is accompanied by a change in any of a number of biological or behavioral measures—even when it is not accompanied by a long-term compromise in an organism's health or capacity to cope with daily challenges—has limited the utility of this concept. This permissive posture, which began with Selye's writings more than 65 years ago, is sustained by the public's desire for a simple term that might explain the tension generated by the threat of terrorists, growing economic inequality, increased competiveness in the workplace or for admission to the best universities, rogue nuclear bombs, and media reports of threats to health in food and water. I believe that the concept stress should be limited to select events that pose a serious threat to an organism's well-being or discarded as too ambiguous to be theoretically useful.